Association of Inflammation with Metabolic Syndrome among Low-Income Rural Kazakh and Uyghur Adults in Far Western China - Yi-Zhong Yan; Ru-Lin Ma; Yu-Song Ding; Heng Guo; Jing-Yu Zhang; La-Ti Mu; Mei Zhang; Jia-Ming Liu; Dong-Sheng Rui; Jia He; Feng Sun; Kui Wang; et al. (Mediators of Inflammation)
This study focused on low-income rural and nomadic minority people residing in China’s far west and investigated their relationship between inflammatory markers (IL-6, hsCRP, FFA, and adiponectin) and MS and ethnic differences. And it found that improving behavioral lifestyle by education or using drugs to control inflammation may prevent MS. These observations may benefit low-income populations.